A current review on animal models of anti-asthmatic drugs screening - Singh, Shivam; Kularia, Sunita; Shukla, Shivakshi; Singh, Mithilesh; Kumar, Manish; Sharma, Ashish Kumar (Frontiers in Pharmacology, 2025)
Asthma is a chronic inflammatory respiratory condition characterised by airway constriction, smooth muscle spasm, and severe morbidity. It affects around 300 million people globally, with children being especially vulnerable. Despite its worldwide effect, the invention of innovative asthma medicines has been slow over the last 5 decades, leaving significant unmet requirements in asthma care. Although intriguing medicines have demonstrated efficacy in animal models, many fail to fulfil safety and effectiveness requirements in human trials, highlighting the critical need for more predictive models that better transfer to human results. This comprehensive review investigates the mechanisms and efficacy of anti-asthmatic drugs using both genetic and conventional animal models. Both genetic and traditional models of anti-asthmatic agents, their characteristics, and their significance are summarized as: In-vitro Models: Histamine receptor assay, Cell Culture Method, WST Assay, Spasmolytic Activity of the Lungs of Guinea Pigs, Airway and Vascular Responses to an Isolated Lung, The Isolated Perfused Guinea Pig Trachea’s Reactivity. In-Vivo Models: In vivo small animal models, Broncho Spasmolytic Activity in anaesthetized Guinea Pigs, Guinea Pigs Respiratory and Vascular Dysfunction Caused by Arachidonic Acid or platelet-activated factor (PAF), Guinea Pig Asphyxia Induced by Serotonin Aerosol and Anaphylactic Microshock, Guinea Pigs Under Anaesthesia: Histamine-Induced Bronchoconstriction, Microshock in Rabbits and Pneumotachography in Guinea Pigs, Guinea Pig Bronchial Hyperactivity, Guinea Pig Airway Microvascular Leakage, Mice With Inflammatory Airways. Conclusion: This review focusses on the benefits and limitations of current animal models in asthma research, emphasising the need for more sophisticated, predictive models to decrease translational failures. By critically evaluating these models, the review emphasises their importance in directing anti-asthmatic drug development and highlights the urgent need for innovation to bridge the gap between preclinical success and clinical efficacy.